2009
DOI: 10.1002/jor.20770
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the long‐head of the biceps tendon are altered in the presence of rotator cuff tears in a rat model

Abstract: Rotator cuff tears are disabling conditions that result in changes in joint loading and functional deficiencies. Clinically, damage to the long-head of the biceps tendon has been found in conjunction with rotator cuff tears, and this damage is thought to increase with increasing tear size. Despite its importance, controversy exists regarding the optimal treatment for the biceps. An animal model of this condition would allow for controlled studies to investigate the etiology of this problem and potential treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 9 publications
(13 reference statements)
3
78
1
3
Order By: Relevance
“…Patients with rotator cuff tears frequently develop long head of the biceps tendon pathology [2], which may lead to increasing pain and loss of function. Previous studies have demonstrated structural long head of the biceps tendon damage in the presence of cuff tears both clinically [13] and in a rat rotator cuff tear model [14]. Commonly, these long head of the biceps tendon symptoms persist and surgeons often will recommend arthroscopic tenodesis or tenotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with rotator cuff tears frequently develop long head of the biceps tendon pathology [2], which may lead to increasing pain and loss of function. Previous studies have demonstrated structural long head of the biceps tendon damage in the presence of cuff tears both clinically [13] and in a rat rotator cuff tear model [14]. Commonly, these long head of the biceps tendon symptoms persist and surgeons often will recommend arthroscopic tenodesis or tenotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The linear region modulus (0.028-0.04 X 1 strain region) was calculated from the 4th cycle of each test, using the cross-sectional area calculated from the thickness measured with a custom laser device and the width between the staple grips. 26 At the peak of the 4th ramp for each test, the deformation gradient tensor (F) was calculated:…”
Section: Biaxial Mechanics Of Angle Ply Laminatesmentioning
confidence: 99%
“…Before testing, cross-sectional area was determined at four locations along the length of each sample with a custom laser-LVDT measurement system. 48 Testing was performed with an Instron 5848 Microtester (Instron, Canton, MA). After a 0.1N preload for 60 s to remove slack, gauge length was noted, and samples were extended to failure at a rate of 0.1% of the gauge length per second.…”
Section: Mechanical Testingmentioning
confidence: 99%